Application of the Self-Potential Method to Determine the Distribution of Leachate in the Manggar TPA Balikpapan - Meidi Arisalwadi; Rahmania Rahmania; Nindi Mayang Oktavia; Nurlaila Ramadhani Hidayah; Febrian Dedi Sastrawan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The Manggar Final Processing Site (TPA) is a TPA located in the city of Balikpapan by implementing a sanitary landfill system. In this system, the waste is piled up into a mountain so that leachate generated from the waste will enter the layers below the surface due to rainwater. To detect the presence or distribution of leachate below the surface, an investigation was carried out using the Self Potential (SP) Method. The results of the data processing obtained are isopotential maps. From this map, we can see the distribution of leachate based on the potential difference value. Based on the slicing data from the anomaly, the value of the potential difference between 31 mV and -50 mV is found, which is scattered towards the north. This can be indicated as a leachate anomaly.